On the antioxidant, neuroprotective and anti-inflammatory properties of S-allyl cysteine: An update. (October 2015) - Colín-González, Ana Laura; Ali, Syed F.; Túnez, Isaac; Santamaría, Abel
Abstract: Therapeutic approaches based on isolated compounds obtained from natural products to handle central and peripheral disorders involving oxidative stress and inflammation are more common nowadays. The validation of nutraceutics vs. pharmaceutics as tools to induce preventive and protective profiles in human health alterations is still far of complete acceptance, but the basis to start more solid experimental and clinical protocols with natural products has already begun. S-allyl cysteine (SAC) is a promising garlic-derived organosulfur compound exhibiting a considerable number of positive actions in cell models and living systems. An update, in the form of review, is needed from time to time to get access to the state-of-the-art on this topic. In this review we visited recent and refreshing evidence of new already proven and potential targets to explain the benefits of using SAC against toxic and pathological conditions. The broad spectrum of protective actions covered by this molecule comprises antioxidant, redox modulatory and anti-inflammatory activities, accompanied by anti-apoptotic, pro-energetic and signaling capacities. Herein, we detail the evidence on these aspects to provide the reader a more complete overview on the promising aspects of SAC in research. Highlights: Aged garlic extract possess antioxidant molecules. S-allyl cysteine (SAC) exhibits protective effects. SAC is neuroprotective at different levels. SAC recruits anti-inflammatory properties.